2017
DOI: 10.2339/politeknik.369019
|View full text |Cite
|
Sign up to set email alerts
|

Metasezgisel Metotlar Kullanılarak Ekonomik Yük Dağıtımı Probleminin Çözümü: Grafiksel Kullanıcı Arayüzü Uygulaması

Abstract: Politeknik Dergisi, 2017; 20 (4) : 827-835 Journal of Polytechnic, 2017; 20 (4) Solution of Economic Dispacth Problem Using Metaheuristic Methods: Graphical User Interface Aplication ABSTRACTThermal power plants play an important role in the electrical energy production. In case these plants work together, determining the optimum point of conditions has a great importance in cost of energy which is produced. Moreover, designing a Graphical User Interface (GUI) enables the results to be easily obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Through this interface, the study solved the ELD problem with Differential Improvement Algorithm (DGA) and Particle Swarm Optimization (PSO) and compared the performances of the algorithms. The results revealed that the PSO algorithm performs better in the ELD problem [12].…”
Section: Introductionmentioning
confidence: 98%
“…Through this interface, the study solved the ELD problem with Differential Improvement Algorithm (DGA) and Particle Swarm Optimization (PSO) and compared the performances of the algorithms. The results revealed that the PSO algorithm performs better in the ELD problem [12].…”
Section: Introductionmentioning
confidence: 98%